Оценка взаимосвязи факторов риска преждевременных родов в различные сроки беременности = Assess of preterm birth risk factors relationship at various pregnancy stages - Aryaev, N. L.; Marichereda, V. G.; Shevchenko, I. M.; Moskalenko, T. Ya.; El Mezevgi, H. M.; Shevchenko, N. V. (Journal of Education, Health and Sport, 2016)
Aryaev N. L., Marichereda V. G., Shevchenko I. M., Moskalenko T. Ya., El Mezevgi H. M., Shevchenko N. V. Оценка взаимосвязи факторов риска преждевременных родов в различные сроки беременности = Assess of preterm birth risk factors relationship at various pregnancy stages. Journal of Education, Health and Sport. 2016;6(9):422-432. eISSN 2391-8306. DOI http://dx.doi.org/10.5281/zenodo.153862 http://ojs.ukw.edu.pl/index.php/johs/article/view/3850 The journal has had 7 points in Ministry of Science and Higher Education parametric evaluation. Part B item 755 (23.12.2015). 755 Journal of Education, Health and Sport eISSN 2391-8306 7 © The Author (s) 2016; This article is published with open access at Licensee Open Journal Systems of Kazimierz Wielki University in Bydgoszcz, Poland Open Access. This article is distributed under the terms of the Creative Commons Attribution Noncommercial License which permits any noncommercial use, distribution, and reproduction in any medium, provided the original author(s) and source are credited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/4.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/4.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. The authors declare that there is no conflict of interests regarding the publication of this paper. Received: 05.08.2016. Revised 25.08.2016. Accepted: 06.09.2016. УДК 618.396 /616-021.1 ОЦЕНКА ВЗАИМОСВЯЗИ ФАКТОРОВ РИСКА ПРЕЖДЕВРЕМЕННЫХ РОДОВ В РАЗЛИЧНЫЕ СРОКИ БЕРЕМЕННОСТИ Н. Л. Аряев1, В. Г. Маричереда1, И. М. Шевченко1, Т. Я. Москаленко1,2, Х. М. Эль-Мезевги1, Н. В. Шевченко2 1Одесский национальный медицинский университет, г. Одесса, Украина 2Родильный дом №7, г. Одесса, Украина Реферат В результате проведения ретроспективного анализа медицинской документации отмечено, что наиболее частыми и статистически значимыми факторами, сопровождающими и обусловливающими преждевременные роды, являются маточные кровотечения, ИЦН, инфекции различной этиологии и локализации, дисфункция плаценты, наличие выкидышей и преждевременных родов в анамнезе, низкий индекс массы тела, гинекологические операции в анамнезе и возраст матери старше 35 лет. В иерархии рисков ПР в сроке до 33 недель первое место занимают маточные кровотечения, затем следуют инфекции различной этиологии и локализации и ИЦН. При ПР в сроке 33-37 недель чаще фиксируется ИЦН, затем следуют маточные кровотечения и дисфункция плаценты. Наличие инфекционного процесса у беременной может привести к ПР в сроке до 33 недель, маточные кровотечения свидетельствуют о возможности наступления ПР до 33 недель. При наличии ИЦН у беременной наступление ПР в 33-37 недель возможно с вероятностью и достоверностью в 71,58%, при дисфункции плаценты вероятность и достоверность равна 62,76%. Маточные кровотечения свидетельствуют о возможности ПР с вероятностью и достоверностью в 57,13%, инфекционный процесс может провоцировать наступление ПР с вероятностью и достоверностью в 52,25%. Ключевые слова: преждевременные роды, факторы риска. ASSESS OF PRETERM BIRTH RISK FACTORS RELATIONSHIP AT VARIOUS PREGNANCY STAGES N. L. Aryaev1, V. G. Marichereda1, I. M. Shevchenko1, T. Ya. Moskalenko1,2, H. M. El Mezevgi1, N. V. Shevchenko2 1Odessa National Medical University, Odessa, Ukraine 2Maternity Hospital №7, Odessa, Ukraine Summary The result of the retrospective analysis of medical records indicated that the most frequent and statistically significant factors that accompany and cause premature labor are uterine bleeding, cervical incompetence, infections of different etiology and localization, dysfunction of placenta, presence of miscarriages and premature births in history, low body mass index, gynecological surgery and history of maternal age older than 35 years. Uterine bleedings rank first in the risk hierarchy of premature births (PB) at the terms up to 33 weeks, and they followed by infection of various etiology and localization and cervical incompetence. When the PR are in 33-37 weeks, cervical incompetence, followed by uterine bleeding and dysfunction of placenta are usually fixed. Infection in a pregnant woman can lead to PR in the period up to 33 weeks, as well as uterine bleeding suggests the possibility of occurrence of PR at the same term. Presence of cervical incompetence in pregnant may result in PB at the terms of 33-37 weeks, with probability and accuracy to 71.58%, while placental dysfunction’s accuracy is 62.76%. Uterine bleeding suggests the possibility of PB with probability and accuracy to 57.13%, infectious can provoke the onset of PB with probability and accuracy to 52.25%. Key words: prematurity, risk factors.